Dependence of Crystallinity and Crystallite Size of Hydroxyapatite from Chicken Eggshell on Calcination Time : A Comparative Study on Scherrer Approach - Arsyad, Ya' Muhammad; Mega Nurhanisa; Elsa Narulita; Ayunda Dwi Handayani; Frinelda Rehulina Barus; Tri Rahma Febrianti Maharani; Hilyana Agis Risla; Latifah Tri Amanda; Delia Amanda; Zahraini Tasya Siregar (UNIB Press, 2025)
The increasing demand for bone graft materials has driven the development of synthetic alternatives that closely mimic the mineral structure of natural bone and dental tissues. Hydroxyapatite (HAp) is a calcium phosphate material whose crystal structure closely resembles that of bone and dental tissue, making it highly suitable for various biomedical applications. In this study, calcium oxide (CaO) was obtained from calcined chicken eggshells, with calcination durations of 2, 3, and 4 hours, followed by the synthesis of HAp using the hydrothermal method at 160 for 24 hours. X-ray diffraction (XRD) analysis was performed to evaluate the effects of calcination time on crystallinity and crystallite size. The results showed that increasing the calcination time led to higher crystallinity, ranging from 46% to 54%. Crystallite size was estimated using three Scherrer-based methods. The straight-line Scherrer method produced values ranging from 1733.17 to 4621.8 nm, the average Scherrer method from 11.33 to 11.74 nm, and the modified Scherrer method from 8.49 to 9.11 nm. All three methods consistently indicated a decrease in crystallite size with longer calcination durations. These findings demonstrate that prolonged calcination enhances crystallinity and reduce crystallite size, underscoring the critical role of calcination time in shaping structural characteristics of HAp.